Generic and sport-specific reactive agility tests assess different qualities in court-based team sport athletes - Scanlan, A. T.; Wen, N.; Kidcaff, A. P.; Berkelmans, D. M.; Tucker, P. S.; Dalbo, V. J. (The Journal of Sports Medicine and Physical Fitness, 2016)
Abstract Aim: Comparisons between reactive agility tests incorporating generic and sport--specific stimuli have been performed only in field-based team sports. The aim of this study was to compare generic (light-based) and sport-specific (live opponent) reactive agility tests in court--based team sport athletes.